Effects of Supportive Educational Program on Anxiety of Mothers of Children Undergoing the Lumbar Puncture (LP) - Mousa Mahdizadeh; akhtar Nejat Mohammad; Hamidreza Behnam Vashani; Tayebeh Reyhani (Mashhad University of Medical Sciences, 2016)
Background: Lumbar Puncture test is one of the most stressful diagnostic procedures in pediatric ward that its prescription put mothers under extreme pressure. There are limited interventions in this regard. Aim: determining the impact of supportive educational program on the anxiety of mothers whose children are undergoing lumbar puncture (LP). Method: the present study is a randomized controlled clinical trial carried out in 2015. Sixty mothers of children undergoing lumbar puncture and hospitalized 3educational hospitals of Mashhad, Iran, were randomly divided to control group (n=30) and intervention group (n=30). The intervention group received supportive program during a session of 60 min. Spielberger State-Trait Anxiety Inventory (STAI) was selected as the research tool. Finally, data were analyzed by Chi-square test, independent t-test using SPSS v.16 software. Results: The mean age of the mothers was 27.3±5.3 and 26.0±3.1, respectively. The mean pre-interventions maternal manifest anxiety was 51.9±6.2 and 53.4±4.3 out of 80, respectively, in the intervention and control groups. The mean post-interventions maternal manifest anxiety was 44.9±5.1 and 52.7±4.2, respectively, in the intervention and control groups. According to the results of independent t-test, significant difference was observed statistically for the mean maternal manifest anxiety between the two groups (p> 0.001). Implications for Practice: Regarding the reduction of maternal anxiety in the intervention group, which is possible because of the attention to the emotional needs of mothers, in addition to proper training; this program can be considered as an effective method to reduce maternal anxiety before the LP test.